Pengaruh Gaya Hidup, Motivasi, Dan Literasi Terhadap Kemampuan Kritis Mahasiswa (Studi Pada Mahasiswa FEB UNISMA) - Alif Satrio Abdullah; Budi Wahono; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This study aims to analyze the influence of lifestyle, motivation, and literacy on the critical thinking skills of students in the Faculty of Economics and Business at the Islamic University of Malang. Using an explanatory quantitative approach, Data were collected from 90 respondents. They were selected through purposive sampling. The data were analyzed using multiple linear regression. This was done via SPSS software. The results indicate that, simultaneously, lifestyle, motivation, and literacy significantly influence critical thinking skills. However, when analyzed individually, only the lifestyle and literacy variables were determined to impact the model positively and significantly, while the motivation variable was not found to have a significant effect. These findings indicate that patterns of productive activities and proficiency in managing information are dominant factors in shaping students’ critical reasoning. The implications of this study emphasize the importance of educational institutions in designing curricula that stimulate academic literacy and support a scientific lifestyle to enhance the intellectual competitiveness of graduates in the global era. Keywords: Critical Thinking, Lifestyle, Literacy, Motivation, Students.